Sustainable Development Practices in Architectural Design for Cultural Inheritance in Chinese Cities - Yan Wang; Keith Kay Hin Tan; Ah-Choo Koo (Wacana Seni Journal of Arts Discourse, 2025)
Cultural heritage plays a crucial role in urban regeneration and sustainable development. In recent years, Chinese cities have encountered mounting challenges in architectural sustainability, particularly in reconciling the demands of modernisation with the preservation of cultural heritage. This study aims to explore architectural design pathways that integrate sustainability with urban cultural inheritance to bridge this critical gap. Based on a systematic literature review and a multi-case study methodology, it develops an integrative framework that combines critical regionalism—as a value orientation that responds to local culture and social identity—with urban catalyst theory as an operational pathway for revitalising public life and cultural vitality. Case data were coded and thematically analysed using ATLAS.ti 9 to test the framework’s applicability and extract transferrable insights. Findings indicate that the sustainable development of Chinese cities benefits from a culture-oriented design approach. Within this paradigm, architecture can achieve a dynamic balance between cultural continuity and modernity through four key strategies: employing materials to sustain heritage, leveraging technology for cultural integration, reinforcing identity and belonging, and optimising spatial structures and organisation. Collectively, these strategies promote the living transmission of urban culture and provide theoretical as well as practical guidance for developing culture-prioritised urban design policies.